A Preliminary Study Of Implementation The Cinemagraph Technique Towards Public Service Announcement (PSA) Of Smoking Habit - Samsudin, Fahmi; Mohd Tajuddin, Rosita; Nik Yusoff, Nik Ridzuan (2016)
This paper studied about the benefits of cinemagaph technique in enhancing public service announcement (PSA) on smoking habit issue. Main objective of this study is to introduce the technique of cinemagraph where it consists of two layers which photo and video that combines together where some parts to be highlighted are animated and loop seamlessly while others remain still. This would serve as the future of new communication through social media by delivering the benefits of contents through this technique. Following this, it serves as a new hybrid image technology by replacing the current poster advertisements in the production phase where the process of printing and making the poster by machines is abolished, because of the technology is replaced by the place through electronic system. Quantitative method has been picked to test the exposure of this technique among respondent, and pilot test been done. Results from the pilot test demonstrate that the self-designed measure is a very much reliable instrument, with an overall Cronbach alpha value of .93. Three factors emerge with high reliability scores of .70 and above. The correlation analysis demonstrates that the entire three dimensions are not perfectly correlated as their correlation analysis illustrates from low to moderate scores. Findings from the analysis confirm the reliability of the scale and validate the influenced results of the perception of public in predicting the existing of cinemagraph technique through the campaign. Results from the study demonstrate that the measurement used in the pilot study can serve as a potential measure in accessing the usability of cinemagraph in Public service announcement (PSA) campaign. The purpose of this paper is to study on the new technique of moving image or cinemagraph as a tool in enhancing current public service announcement (PSA) of smoking habit in Malaysia, thus can help industry of advertising to perform the campaign in order to spread the message of hazardous of smoking towards the target group in interactive way.